ChemInform Abstract: Transition Metal‐Participated Synthesis and Utilization of N‐Containing Heterocycles: Exploring for Nitrogen Sources. Issue 33 (27th July 2016) - Gao, Mingchun; Xu, Bin
Abstract: Review: [37 refs.